Radio of Flesh and Bone: Community Radio in the Authoritarian and Patriarchal Context of Today’s Nicaragua - DeGrave, Analisa (Conjunctions. Transdisciplinary Journal of Cultural Participation, 2024)
In A Passion for Radio: Training of Trainers José Ignacio López Vigil asserts that community radio “is (made) of flesh and bone” (2015, p. 25). In the context of authoritarianism and patriarchy in today’s Nicaragua these words suggest at least three meanings. One recalls threats to the lives and livelihoods of Nicaraguans that work for Nicaragua’s surviving independent media, including community radio, particularly following the political and humanitarian crisis that began in April 2018. Community radio as “flesh and bone” also relates to the bodies of its listening public and is examined in this paper through the prism of the feminist community radio station, Radio Vos (Radio You 101.7 FM). Radio as “flesh and bone” also serves as a metaphor for community radio’s material and operational existence, a body that functions via multiple interworking parts and systems. In discussing the challenges facing community radio in Nicaragua, this essay incorporates excerpts from an interview with Argentina Olivas, the director of Radio Vos.